2017
DOI: 10.1371/journal.pone.0180865
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol ameliorates diet-induced dysregulation of lipid metabolism in zebrafish (Danio rerio)

Abstract: Defective lipid metabolism is associated with increased risk of various chronic diseases, such as obesity, cardiovascular diseases, and diabetes. Resveratrol (RSV), a natural polyphenol, has been shown the potential of ameliorating disregulations of lipid metabolism. The objective of this study was to investigate the effects of feed intake and RSV on lipid metabolism in zebrafish (Danio rerio). The adult males were randomly allocated to 6 groups: control (Con, 8 mg cysts/fish/day), control with 20 μmol/L RSV (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…Our future study should confirm their exact structures. Our results indicated that αMR may exert its anti-obesity effects via circulating quercetin metabolites, perhaps by regulating the AMPKα-Sirt1-PPARγ pathway and TRPV1 channels [9,10]. We are designing studies to investigate these effects.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our future study should confirm their exact structures. Our results indicated that αMR may exert its anti-obesity effects via circulating quercetin metabolites, perhaps by regulating the AMPKα-Sirt1-PPARγ pathway and TRPV1 channels [9,10]. We are designing studies to investigate these effects.…”
Section: Discussionmentioning
confidence: 92%
“…Green tea catechins, cacao oligomeric procyanidins, and glucomannan have been shown to reduce lipid absorption [5][6][7][8]. Resveratrol, a natural polyphenolic compound found in berries, has been shown to regulate lipid metabolism through AMP-activated protein kinase α (AMPKα), silent information regulator 2 homolog 1 (Sirt1), and the peroxisome proliferator-activated receptor γ (PPARγ) pathway in zebrafish [9]. Chili pepper capsaicin has been reported to activate transient receptor potential cation channel sub-family V member 1 (TRPV1) channels and reduce energy expenditure directly by activating brown adipose tissue [10].…”
mentioning
confidence: 99%
“…A similar effect was observed in our previous study, where RV only enhanced the hepatic enzyme production of the ∆6-desaturase, a key enzyme in LC-PUFA synthesis, when trout were fed diets lacking fish oil (Torno et al, 2017). A bi-directional interaction of RV with the lipid metabolism of zebra fish has been recently investigated (Ran et al, 2017). The n-3 LC-PUFA enhancing effects of RV could be additionally mediated through a direct impact on other elongases and desaturases in the FA synthesis (Momchilova et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we summarize the effect of resveratrol on SIR1 regulation in lifespan and health benefit. In the overfed zebrafish model, resveratrol modulates lipid metabolism by activating the AMPKα‐Sirt1‐PPARγ pathway . Resveratrol ameliorates aging‐related metabolic phenotypes by suppressing cyclic adenosine monophosphate (cAMP), phosphodiesterases (PDEs) leading to elevated cAMP levels in diet‐induced obesity mice .…”
Section: The Effect Of Resveratrol and Pterostilbene On Age‐related Mmentioning
confidence: 99%